Comparative advantage in Bangladesh crop production - Shahabuddin, Quazi; Dorosh, Paul A. (International Food Policy Research Institute, 2002)
This study uses data from 1996/97 through 1998/99 to examine the relative efficiency of production of crops in Bangladesh and their comparative advantage in international trade as measured by net economic profitability (the profitability using economic, rather than financial costs and prices), and the domestic resource cost ratio, (the amount of value of non-tradable domestic resources used in production divided by the value of tradable products). The economic profitability analysis demonstrates that Bangladesh has a comparative advantage in domestic production of rice for import substitution. However, at the export parity price, economic profitability of rice is generally less than economic profitability of many non-rice crops, implying that Bangladesh has more profitable options other than production for rice export. Several non-cereal crops, including vegetables, potatoes and onions have financial and economic returns that are as high as or higher than those of High Yielding Variety (HYV) rice. The relatively minor role in cropping systems of these crops despite their higher returns, can largely be attributed to high price risks associated with marketing, suggesting the need for further development of agro-processing industries, rural infrastructure, and marketing networks. -- Authors Abstract